Scopus based bibliometric analysis of margarine for the period of 2012-2021 - Sarvar Khodjaev; Shakhnozakhon Salijonova; Madina Khamidova; Alvina Farooqui (Hasanuddin University Food Science and Technology Study Program, 2026)
Margarine is an important fat-based food product widely consumed worldwide, and its formulation has evolved toward improved nutritional and functional properties. This study aimed to perform a bibliometric analysis of margarine-related scientific publications indexed in the Scopus database over the period 2012-2021. The data were collected using the keyword “margarine” in titles, abstracts, and keywords, followed by filtering based on subject area, language, and publication period. A total of 204 publications were selected and analyzed using Microsoft Excel and VOSviewer to evaluate publication trends, leading countries, authors, journals, funding organizations, and keyword co-occurrence networks. The results showed a gradual increase in publications, with a noticeable rise in 2020-2021. Research articles accounted for 87% of all publications, indicating the experimental nature of studies in this field. The United States and Brazil were identified as the leading contributors, while journals such as Food Chemistry and Nutrients demonstrated high citation impact. Co-authorship and keyword analyses revealed limited international collaboration and a strong focus on topics such as trans-fat reduction, functional ingredients, and fat substitutes. In conclusion, although the number of publications has increased in recent years, the overall volume of research remains limited. The findings highlight the need for stronger international collaboration, increased research funding, and further studies aimed at improving the quality and functionality of margarine products.